2008
DOI: 10.1039/b809521c
|View full text |Cite
|
Sign up to set email alerts
|

Methanolysis of 4-bromobenzenediazonium ions. Effects of acidity, [MeOH] and temperature on the formation and decomposition of diazo ethers that initiate homolytic dediazoniation

Abstract: We have investigated the effects of solvent composition, acidity and temperature on the dediazoniation of 4-bromobenzenediazonium (4BrBD) ions in MeOH-H(2)O mixtures by employing a combination of spectrometric and chromatographic techniques. The kinetic behaviour is quite complex; in the absence of MeOH, dediazoniations follow first-order kinetics with a half-life t(1/2) approximately 3000 min (T = 45 degrees C), but addition of small concentrations of MeOH lead to more rapid but non-first-order kinetics, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…1 can be derived where k HET and k HOM are the rate constants for the spontaneous thermal heterolytic decomposition of ArN þ 2 and the decomposition of the diazo ether, respectively, with K standing for the equilibrium constant for the diazo ether formation shown in the Scheme. [5] and confirming that increasing concentrations of EtOH have opposing effects upon the formation of the diazo ether in this concentration range: it is favored modestly by higher concentrations of EtOH through the mass-action effect, but strongly opposed by the medium effect on the equilibrium constant.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…1 can be derived where k HET and k HOM are the rate constants for the spontaneous thermal heterolytic decomposition of ArN þ 2 and the decomposition of the diazo ether, respectively, with K standing for the equilibrium constant for the diazo ether formation shown in the Scheme. [5] and confirming that increasing concentrations of EtOH have opposing effects upon the formation of the diazo ether in this concentration range: it is favored modestly by higher concentrations of EtOH through the mass-action effect, but strongly opposed by the medium effect on the equilibrium constant.…”
mentioning
confidence: 52%
“…Formation of the diazo ether is exothermic yet has a positive standard free energy of formation at any of the temperatures investigated. The Gibbs free energy DG is higher for 70% EtOH/H 2 O than for 35% EtOH/H 2 O, highlighting the opposing effects of the concentration of EtOH, as it was previously found in solvolytic dediazoniations [4] [5].…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…In nonaqueous solvents, products associated with free radicals, for example, biphenyl derivatives and replacement of N 2 + by H are often observed, especially when electron-withdrawing groups are present on the arenediazonium ion [4,[17][18][19][20][21]. In this context heterolytic dediazoniation has been reported to occur with ortho-, meta-and para-methylbenzenediazonium (2MBD, 3MBD, 4MBD) and para-nitrobenzenediazonium (4NBD) ions in an aqueous medium [10,22], while other authors interpreted their results as showing evidence of heterolytic and homolytic processes during the thermal and photochemical dediazoniation of several arenediazonium ions in trifluoroethanol and ethanol [19][20][21]. However, in our latest article, we demonstrated that, at moderate pH, water can act as nucleophile giving rise to a diazohydroxide, which eventually can decompose to give radical products [23].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of arenediazonium salts is also modulated by the nature and position of substituents in the aromatic ring . In aqueous solution, electron‐withdrawing substituents make arenediazonium ions to be more stable than those with electron‐releasing groups but make them more prone to react through radical pathways …”
Section: Introductionmentioning
confidence: 99%